Effect of low power laser on osteogenic proliferation of human umbilical cord mesenchymal stem cells (Research, Society and Development, 2022)
This work aims to evaluate the effect of Low Power Laser at red wavelength of 660nm on osteogenic proliferation of human umbilical cord mesenchymal stem cells. Processing of the cord was performed, consisting of sectioning the cord into fragments; washing with the solution; separation and discarding of the stromal vessels; sectioning of the remaining jelly and placement in culture bottles with DMEM medium supplemented with 15% SFB, 20% Ham F-12 Gibco® and antibiotics and kept in a CO2 oven at 37º C and 5% CO2; The culture medium was changed in 24h and 7 days, after this period it was changed every 72h, until the spontaneous migration of cells to the surface; when 80% confluence was reached. The cells were used in the third passage, where they were trypsinized, resuspended, and the number of cells was counted for plating in 96 wells. 24 hours after plating, the differentiation inducers were inserted, and the cells belonging to the LBP groups were irradiated. The proliferation curve was performed by the MTT assay. Solution containing 0.5 mg MTT per mL of medium was added, after incubation at 37 °C for 4 h protected from light, DMSO will be added to the cells. The absorbance was read by spectrophotometer at 562 nm at 24, 48 and 72 h to establish cell proliferation curve. The proliferation of MSCs was higher in cells submitted to the regular medium and LBP showed a positive effect on the proliferation of MSCs associated with the osteogenic medium.